Analysis of the Effect of Transformational Leadership, Job Satisfaction, and Employee Engagement on Company Performance: A Study on Manufacturing Industry in Jakarta - Mislan Sihite; Agus Yulistiyono; KRT. Akhir Lusono; Eva Yuniarti Utami (Westscience Press, 2023)
This research investigates the dynamic interplay between transformational leadership, job satisfaction, employee engagement, and company performance within the manufacturing industry in Jakarta. A comprehensive quantitative analysis involving a sample of 250 participants reveals crucial insights into the relationships among these key variables. The results highlight the significant and positive impact of transformational leadership, job satisfaction, and employee engagement on company performance. The study employs structural equation modeling to assess the measurement and structural models, providing a robust foundation for understanding the complex organizational dynamics in the context of Jakarta's manufacturing sector. The findings contribute to both theoretical frameworks and practical implications for organizational leaders, fostering a deeper understanding of the factors that drive success in this industry.